2009
DOI: 10.17221/3044-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine response and clinicopathological findings in Brucella infected camels (Camelus dromedarius)

Abstract: The present study had the aim of assessing the cytokine response and selected clinicopathological findings associated with brucellosis in camels (Camelus dromedarius). 340 dromedary camels were examined for brucellosis using agglutination and Complement Fixation tests (CFT). Twenty-five camels (7.35%) were positive by both tests; 14 (4.12%) for B. abortus and 11 (3.23%) for B. melitensis. IL-1β and IL-10 interleukin levels in both B. abortus and B. melitensis infected camels showed significant elevations (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
7
20
0
Order By: Relevance
“…Furthermore, cows serologically positive for brucellosis had lower A/G ratios when compared with healthy cows. The result of the present study is partly in agreement with previous reports that documented an increase of serum globulin level in Brucella-affected cows (18), ewes (31), and camels (19), whereas Nath et al (18) reported a significant decrease in albumin concentrations and nonsignificant changes in total protein and A/G ratio between the brucellosis-affected and healthy cows. However, Hamada et al (31) found a nonsignificant difference in albumin and total protein between brucellosis-affected and healthy ewes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, cows serologically positive for brucellosis had lower A/G ratios when compared with healthy cows. The result of the present study is partly in agreement with previous reports that documented an increase of serum globulin level in Brucella-affected cows (18), ewes (31), and camels (19), whereas Nath et al (18) reported a significant decrease in albumin concentrations and nonsignificant changes in total protein and A/G ratio between the brucellosis-affected and healthy cows. However, Hamada et al (31) found a nonsignificant difference in albumin and total protein between brucellosis-affected and healthy ewes.…”
Section: Discussionsupporting
confidence: 93%
“…However, Hamada et al (31) found a nonsignificant difference in albumin and total protein between brucellosis-affected and healthy ewes. El-Boshy et al (19) reported a significant decrease in serum albumin between brucellosis-affected and healthy camels.…”
Section: Discussionmentioning
confidence: 99%
“…El-Boshy et al [32] reported significant increases (P<0.05) in serum SD, AST and ALT levels and non-significant variations in creatinine in Brucella infected animals. Forbes et al [31] confirmed stable and similar haemato-biochemical parameters in moose experimentally infected with B. abortus biovar 1.…”
Section: /5mentioning
confidence: 96%
“…Some worker has also reported higher Hb concentration in Brucella infected animals [32]. Lymphocyte count was also lowered in Brucella infected animals [32,33]. However, Sikder et al [30] found higher values of neutrophil, monocyte and eosinophil counts in the B. abortus positive cattle than the standard values.…”
Section: /5mentioning
confidence: 99%
See 1 more Smart Citation